A preparation process for a corrosion-resistant external reflector housing
By using modified polyimide and other materials and advanced processes, corrosion-resistant external mirror shells are prepared, which solves the aging problem of traditional mirror shells under the action of ultraviolet rays and corrosive media, and significantly improves corrosion resistance and service life.
Patent Information
- Application Number
- CN202411961936.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional reflector housing materials are prone to aging under ultraviolet irradiation and corrosive media, resulting in reduced corrosion resistance and safety, frequent maintenance and replacement, increasing the cost of use.
Materials such as modified polyimide, fluoroelastomer micro powder, nanotitanium dioxide, graphene nanosheets, organic montmorillonite, hindered phenol antioxidants, benzotriazole ultraviolet absorbers, polyether modified silicone oil lubricants and rare earth metal organic complexes are prepared through high-speed mixing, twin-screw extrusion and vacuum drying.
It significantly improves the corrosion resistance, stain resistance and durability of the reflector shell, extends the service life, reduces maintenance costs and frequency, and allows the product to maintain good performance in a complex and changeable external environment.
Smart Images

Figure CN119748744A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of automobile reflector production, and in particular relates to a preparation process of a corrosion-resistant external reflector shell. Background Art
[0002] With the rapid development of the automobile industry and various types of outdoor transportation tools and equipment, the performance requirements of external reflectors, as key components to ensure driving safety and equipment operation safety, are becoming increasingly stringent. Among the many performance indicators, the corrosion resistance of the shell is particularly important, because the reflector shell is exposed to the outdoor environment for a long time during actual use, facing the combined effects of multiple complex factors such as ultraviolet radiation, temperature changes, humidity fluctuations, acid rain erosion, road dust, oil pollution, etc. In some special environments, such as the seaside, near chemical parks, or in high-humidity, high-pollution urban areas, the corrosion resistance problem of traditional reflector shells is more prominent. Frequent maintenance and replacement of reflector shells not only increases the cost of use, but also causes inconvenience and delays to the normal operation of vehicles or equipment. Therefore, the development of an external reflector shell material with excellent corrosion resistance has become a key technical problem that the industry needs to solve urgently.
[0003] However, traditional mirror shell materials are prone to aging under long-term exposure to ultraviolet rays, which leads to reduced material strength and affects the overall structural stability of the mirror. At the same time, when faced with corrosive media such as acid rain, road salt and oil pollution, their corrosion resistance is limited, reducing the safety and reliability of the mirror. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation process of a corrosion-resistant external reflector housing in order to solve the above-mentioned problem.
[0005] The technical solution adopted by the present invention is as follows: a preparation process of a corrosion-resistant external reflector housing, the preparation process comprising the following steps:
[0006] S1: First, weigh the raw materials for preparation, and weigh: 30-40 parts by weight of modified polyimide; 15-20 parts by weight of fluororubber powder; 10-15 parts by weight of nano titanium dioxide; 5-10 parts by weight of graphene nanosheets; 4-8 parts by weight of organic montmorillonite; 0.5-0.8 parts by weight of hindered phenol antioxidant; 0.3-0.6 parts by weight of benzotriazole ultraviolet absorber; 0.2-0.4 parts by weight of polyether modified silicone oil lubricant and 0.3-0.7 parts by weight of rare earth metal organic complex;
[0007] S2: Put the weighed modified polyimide, fluororubber powder and organic montmorillonite into a high-speed mixer, and stir at a speed of 800 to 1200 rpm for 5 to 10 minutes to preliminarily mix the components;
[0008] S3: Then, the nano-titanium dioxide and graphene nanosheets are slowly added to the high-speed mixer, and the speed is adjusted to 1000-1500 rpm, and stirring is continued for 8-15 minutes to ensure that the nano-materials are evenly dispersed in the mixture to prevent agglomeration;
[0009] S4: Add hindered phenol antioxidant, benzotriazole UV absorber, polyether modified silicone oil lubricant and special functional additive rare earth metal organic complex into a high-speed mixer in sequence, and stir at a speed of 1200 to 1800 rpm for 3 to 8 minutes to fully blend all additives with the previous mixture;
[0010] S5: conveying the uniformly mixed materials to the hopper of a twin-screw extruder through a vacuum feeding device, setting the screw aspect ratio of the twin-screw extruder to 30-40:1, setting the temperature of each zone to 280-320° C., and controlling the screw speed to 200-300 rpm to perform melt blending, extrusion and granulation to obtain modified plastic particles;
[0011] S6: placing the extruded granulated particles in a vacuum drying oven and drying them at 80-100° C. for 4-6 hours to remove moisture and residual volatiles in the particles to ensure the stability of subsequent processing and product quality;
[0012] S7: adding the dried particles into the barrel of an injection molding machine, setting the barrel temperature of the injection molding machine to 300-350° C., controlling the mold temperature to 80-120° C., setting the injection pressure to 60-100 MPa, adjusting the injection speed to 30-60 mm / s, and performing an injection molding operation to obtain a blank of an external reflector housing;
[0013] S8: Deburring the blank after injection molding, such as by grinding, polishing and other processes, to make the shell surface smooth and flat without obvious defects and flash;
[0014] S9: Perform quality inspection on the mirror housing after deburring, including appearance inspection (for cracks, deformation, color difference, etc.), dimensional accuracy measurement (compared with design drawing requirements) and performance testing (such as corrosion resistance test, impact resistance test, etc.). Qualified products are packaged and put into storage, and unqualified products are classified and marked, and the reasons are analyzed. They are reworked or scrapped as appropriate.
[0015] In a preferred embodiment, in step S1, the hindered phenol antioxidant is antioxidant 1076 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate);
[0016] Benzotriazole UV absorbers such as UV absorber UV-329 (2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole);
[0017] The rare earth metal organic complex can be a complex formed by a rare earth lanthanide metal (such as lanthanum, cerium, etc.) and an organic ligand (such as acetylacetone, citric acid, etc.).
[0018] In a preferred embodiment, in step S2, the mixing chamber of the high-speed mixer is cleaned and dried in advance to prevent impurities from mixing in and affecting material properties; the mixer blades are designed with a specific forward tilt angle of 30 degrees and a twist of 45 degrees, which can generate strong convection and shear force when rotating, ensuring that the three raw materials are initially evenly dispersed in a relatively short time; the mixing process is carried out in a closed environment to reduce the contact between the raw materials and the outside air and prevent moisture absorption or oxidation from causing changes in the raw material properties.
[0019] In a preferred embodiment, in step S3, when adding the nanomaterial, a high-precision micro-feeding device is used to accurately control the feeding amount at a speed of 2 g / s, so that the nanomaterial slowly and evenly enters the material flow in the high-speed mixer; since the nanomaterial has a large specific surface area and high surface energy and is easy to agglomerate, nitrogen is intermittently introduced during the stirring process, and the gas flow rate is stabilized at 8 liters / minute. The agglomerates that may be formed are broken up by air flow disturbance, while protecting the raw materials from oxidation.
[0020] In a preferred embodiment, in step S4, when adding additives, the addition interval of each additive is set to 1.5 minutes so that the previous additive can be better dispersed in the material; during the high-speed stirring process, the temperature inside the mixer rises due to frictional heat, and the temperature is controlled by the cooling jacket to maintain the mixing temperature at 50°C to prevent the additives from decomposing or volatilizing due to high temperature, thereby ensuring that their effective ingredients can fully exert their effects.
[0021] In a preferred embodiment, in the step S5, the screw structure of the twin-screw extruder adopts a specific combined design, including a conveying section using equidistant and unequal depth thread elements, a mixing section using a combination of kneading blocks and reverse thread elements, and a homogenizing section using toothed disc elements. The geometric shape and arrangement of the screw elements in each section are optimized according to the material properties to achieve efficient melting, mixing and homogenization effects; during the extrusion process, the vacuum degree is maintained at -0.07MPa to remove bubbles and volatiles in the material and improve the density and quality stability of the particles.
[0022] In a preferred embodiment, in step S6, the vacuum system of the vacuum drying oven adopts a combination of a vacuum pump and a 50-liter vacuum buffer tank to stably maintain the vacuum degree in the drying oven; 6 layers of shelves are arranged inside the drying oven, and the particles are evenly spread on the shelves, and the layer spacing is maintained at 8 cm to ensure uniform heat transfer and sufficient volatilization of moisture; the drying oven is equipped with a temperature sensor and a humidity sensor to monitor and control the temperature and humidity changes during the drying process in real time to ensure the best drying effect.
[0023] In a preferred embodiment, in the step S7, the barrel of the injection molding machine adopts zoned heating control, and is divided into 5 heating zones from the hopper end to the nozzle end, and the temperatures of each zone are set to 280°C, 300°C, 320°C, 330°C, and 340°C, respectively, to ensure that the material is evenly heated and gradually melted in the barrel, and injected into the mold cavity at a suitable temperature and pressure; the mold is manufactured using a high-precision processing technology, the mold surface is polished and chrome-plated, and the surface roughness reaches Ra1.2 microns, ensuring that the surface of the shell after injection molding is smooth, easy to demold and has good appearance quality.
[0024] In a preferred embodiment, in step S8, according to the shape and precision requirements of different parts of the shell, 150-mesh coarse sandpaper is first used to remove larger burrs and burrs, and then 400-mesh fine sandpaper is used for fine grinding to make the surface roughness reach Ra0.6 microns; the polishing process uses a polishing paste and a polishing wheel, and the polishing wheel speed is controlled at 2000 rpm. By adjusting the polishing time to 10 minutes and the pressure to 0.5 MPa, the shell surface achieves a mirror gloss effect to meet the appearance decorative requirements.
[0025] In a preferred embodiment, in step S9, the dimensional accuracy measurement adopts a high-precision three-dimensional coordinate measuring instrument to accurately measure the key dimensions of the shell (such as length, width, thickness, aperture, etc.), and the measurement accuracy can reach ±0.01 mm. The measurement result is compared with the tolerance requirements of the design drawing to determine whether it is qualified; the corrosion resistance test adopts a corrosion test box that simulates the actual use environment, and the shell is placed in a mist environment containing corrosive media such as 5% sulfuric acid, 3% sodium hydroxide and 5% sodium chloride. The test time lasts for 480 hours, and the degree of corrosion on the surface of the shell is observed, and the corrosion resistance level is evaluated according to relevant standards; the impact resistance test uses a drop hammer impact tester, with a 1 kg drop hammer freely falling from a height of 1 meter to impact a specific part of the shell, and observe whether the shell is broken or permanently deformed, so as to evaluate whether its impact resistance meets the requirements.
[0026] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0027] 1. In the present invention, the tiny particles of nano-titanium dioxide and graphene nanosheets are intertwined and interspersed with each other, avoiding the occurrence of agglomeration, so that the subsequent molding process can be carried out smoothly based on a uniform raw material basis, ensuring the consistency and stability of product quality. In the melt blending stage, it undergoes a high-temperature plasticization process together with other materials such as modified polyimide. The ultraviolet shielding function of nano-titanium dioxide can effectively reduce the damage of ultraviolet rays to the molecular chain of the material in this process, maintain the stability of the material system, prevent abnormal changes in melt viscosity caused by light aging, and ensure the continuity and efficiency of the extrusion granulation process. At the same time, the high thermal conductivity of graphene nanosheets helps to transfer heat evenly in the material, avoid local overheating causing material performance differences, and is conducive to the formation of high-quality modified plastic particles, greatly extending the service life of the reflector housing and reducing maintenance costs.
[0028] 2. In the present invention, in the injection molding process, the combination of nano-titanium dioxide and graphene nanosheets enhances the fluidity and filling of the material, so that the material can fill the mold cavity more accurately, reduce molding defects, and improve the dimensional accuracy and appearance quality of the product. During the use of the molded shell, the photocatalytic self-cleaning properties of nano-titanium dioxide and the antistatic and high-strength properties of graphene nanosheets continue to play a role. The photocatalytic effect keeps the shell surface clean and reduces the adhesion of corrosive media. The antistatic property prevents dust from adsorbing and carrying corrosive substances. The high strength ensures the stability of the shell structure, which significantly improves the corrosion resistance, stain resistance and durability of the shell, greatly prolongs the service life of the reflector shell, reduces the maintenance cost and frequency, and enables the product to always maintain good performance in a complex and changeable external environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the process principle of the present invention. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] Embodiment 1:
[0032] Reference Figure 1 ,
[0033] A preparation process for a corrosion-resistant external reflector housing, the preparation process comprising the following steps:
[0034] S1: First, weigh the raw materials for preparation, and weigh: 30 parts by weight of modified polyimide; 15 parts by weight of fluororubber powder; 10 parts by weight of nano titanium dioxide; 5 parts by weight of graphene nanosheets; 4 parts by weight of organic montmorillonite; 0.5 parts by weight of hindered phenol antioxidant; 0.3 parts by weight of benzotriazole ultraviolet absorber; 0.2 parts by weight of polyether modified silicone oil lubricant and 0.3 parts by weight of rare earth metal organic complex;
[0035] S2: Put the weighed modified polyimide, fluororubber powder and organic montmorillonite into a high-speed mixer, and stir at a speed of 800 to 1200 rpm for 5 to 10 minutes to preliminarily mix the components.
[0036] S3: Then, the nano-titanium dioxide and graphene nanosheets are slowly added into the high-speed mixer, and the rotation speed is adjusted to 1000-1500 rpm, and stirring is continued for 8-15 minutes to ensure that the nano-materials are evenly dispersed in the mixture to prevent agglomeration.
[0037] S4: Add hindered phenol antioxidant, benzotriazole UV absorber, polyether modified silicone oil lubricant and special functional additive rare earth metal organic complex into the high-speed mixer in sequence, and stir at a speed of 1200-1800 rpm for 3-8 minutes to fully blend all additives with the previous mixture.
[0038] S5: The uniformly mixed material is conveyed to the hopper of a twin-screw extruder through a vacuum feeding device, the screw aspect ratio of the twin-screw extruder is set to 30-40:1, the temperature of each zone is set at 280-320°C, the screw speed is controlled at 200-300 rpm, and melt blending extrusion granulation is performed to obtain modified plastic particles.
[0039] S6: Place the extruded granules in a vacuum drying oven and dry them at 80-100°C for 4-6 hours to remove moisture and residual volatiles in the particles to ensure the stability of subsequent processing and product quality.
[0040] S7: Add the dried particles into the barrel of an injection molding machine, set the barrel temperature of the injection molding machine to 300-350° C., control the mold temperature to 80-120° C., set the injection pressure to 60-100 MPa, adjust the injection speed to 30-60 mm / s, perform injection molding operation, and obtain a blank of an external reflector housing.
[0041] S8: Deburr the blank after injection molding by grinding, polishing and other processes to make the shell surface smooth and flat without obvious defects and flash.
[0042] S9: Perform quality inspection on the mirror housing after deburring, including appearance inspection (for cracks, deformation, color difference, etc.), dimensional accuracy measurement (compared with design drawing requirements) and performance testing (such as corrosion resistance test, impact resistance test, etc.). Qualified products are packaged and put into storage, and unqualified products are classified and marked, and the reasons are analyzed. They are reworked or scrapped as appropriate.
[0043] In step S1, the hindered phenol antioxidant is antioxidant 1076 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate).
[0044] Benzotriazole UV absorbers such as UV absorber UV-329 (2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole);
[0045] Rare earth metal organic complexes can be complexes formed by rare earth lanthanide metals (such as lanthanum, cerium, etc.) and organic ligands (such as acetylacetone, citric acid, etc.)
[0046] In step S2, the mixing chamber of the high-speed mixer is cleaned and dried in advance to prevent impurities from mixing in and affecting the material properties. The mixer blades are designed with a specific forward tilt angle of 30 degrees and a twist of 45 degrees, which can generate strong convection and shear force when rotating, ensuring that the three raw materials are initially evenly dispersed in a short time. The mixing process is carried out in a closed environment to reduce the contact between the raw materials and the outside air and prevent moisture absorption or oxidation from causing changes in the raw material properties.
[0047] In step S3, when adding the nanomaterial, a high-precision micro-feeding device is used to accurately control the feeding amount at a speed of 2 g / s, so that the nanomaterial slowly and evenly enters the material flow in the high-speed mixer. Since the nanomaterial has a large specific surface area and high surface energy and is easy to agglomerate, nitrogen is intermittently introduced during the stirring process, and the gas flow rate is stabilized at 8 liters / minute. The agglomerates that may be formed are broken up by air flow disturbance, while protecting the raw materials from oxidation.
[0048] In step S4, when adding additives, the interval between adding each additive is set to 1.5 minutes so that the previous additive can be better dispersed in the material. During high-speed stirring, the temperature inside the mixer rises due to frictional heat. The temperature is controlled by the cooling jacket to maintain the mixing temperature at 50°C to prevent the additives from decomposing or volatilizing due to high temperature, ensuring that their effective ingredients can fully exert their effects.
[0049] In step S5, the screw structure of the twin-screw extruder adopts a specific combined design, including the conveying section adopting equidistant and unequal depth thread elements, the mixing section adopting a combination of kneading blocks and reverse thread elements, and the homogenizing section adopting toothed disc elements. The geometric shape and arrangement of the screw elements in each section are optimized according to the material characteristics to achieve efficient melting, mixing and homogenization effects. During the extrusion process, the vacuum degree is maintained at -0.07MPa to remove bubbles and volatiles in the material and improve the density and quality stability of the particles.
[0050] In step S6, the vacuum system of the vacuum drying oven uses a vacuum pump combined with a 50-liter vacuum buffer tank to stably maintain the vacuum degree in the drying oven. Six shelves are set inside the drying oven, and the particles are evenly spread on the shelves, with a layer spacing of 8 cm to ensure uniform heat transfer and full volatilization of moisture. The drying oven is equipped with a temperature sensor and a humidity sensor to monitor and control the temperature and humidity changes during the drying process in real time to ensure the best drying effect.
[0051] In step S7, the barrel of the injection molding machine adopts zone heating control, which is divided into 5 heating zones from the hopper end to the nozzle end. The temperature of each zone is set to 280℃, 300℃, 320℃, 330℃, and 340℃ respectively, to ensure that the material is evenly heated and gradually melted in the barrel, and injected into the mold cavity at the appropriate temperature and pressure. The mold is manufactured using high-precision processing technology, and the mold surface is polished and chrome-plated. The surface roughness reaches Ra1.2 microns, ensuring that the shell surface after injection molding is smooth, easy to demold, and has good appearance quality.
[0052] In step S8, according to the shape and precision requirements of different parts of the shell, 150-mesh coarse sandpaper is first used to remove large flash and burrs, and then 400-mesh fine sandpaper is used for fine grinding to make the surface roughness reach Ra0.6 microns. The polishing process uses polishing paste and polishing wheel, and the polishing wheel speed is controlled at 2000 rpm. By adjusting the polishing time to 10 minutes and the pressure to 0.5MPa, the shell surface achieves a mirror gloss effect to meet the appearance decorative requirements.
[0053] In step S9, a high-precision three-dimensional coordinate measuring instrument is used for dimensional accuracy measurement to accurately measure the key dimensions of the shell (such as length, width, thickness, aperture, etc.). The measurement accuracy can reach ±0.01 mm. The measurement results are compared with the tolerance requirements of the design drawings to determine whether they are qualified. The corrosion resistance test uses a corrosion test chamber that simulates the actual use environment. The shell is placed in a mist environment containing corrosive media such as 5% sulfuric acid, 3% sodium hydroxide, and 5% sodium chloride. The test lasts for 480 hours, and the degree of corrosion on the surface of the shell is observed. The corrosion resistance level is assessed according to relevant standards. The impact resistance test uses a drop hammer impact tester to drop a 1 kg drop hammer freely from a height of 1 meter to impact a specific part of the shell to observe whether the shell is broken or permanently deformed, so as to evaluate whether its impact resistance meets the requirements.
[0054] In the present invention, the tiny particles of nano-titanium dioxide and graphene nanosheets are intertwined and interspersed with each other, avoiding the occurrence of agglomeration, so that the subsequent molding process can be carried out smoothly based on a uniform raw material basis, ensuring the consistency and stability of product quality. In the melt blending stage, together with other materials such as modified polyimide, the ultraviolet shielding function of nano-titanium dioxide can effectively reduce the damage of ultraviolet rays to the material molecular chain in this process, maintain the stability of the material system, prevent the abnormal change of melt viscosity caused by light aging, and ensure the continuity and efficiency of the extrusion granulation process. At the same time, the high thermal conductivity of graphene nanosheets helps the uniform transfer of heat in the material, avoids local overheating and causes material performance differences, and is conducive to the formation of high-quality modified plastic particles.
[0055] In the present invention, in the injection molding process, the combination of nano-titanium dioxide and graphene nanosheets enhances the fluidity and filling of the material, so that the material can fill the mold cavity more accurately, reduce molding defects, and improve the dimensional accuracy and appearance quality of the product. During the use of the molded shell, the photocatalytic self-cleaning properties of nano-titanium dioxide and the antistatic and high-strength properties of graphene nanosheets continue to play a role. The photocatalytic effect keeps the shell surface clean and reduces the adhesion of corrosive media. The antistatic property prevents dust from adsorbing and carrying corrosive substances. The high strength ensures the stability of the shell structure, which significantly improves the corrosion resistance, stain resistance and durability of the shell, greatly prolongs the service life of the reflector shell, reduces the maintenance cost and frequency, and enables the product to always maintain good performance in a complex and changeable external environment.
[0056] Embodiment 2:
[0057] Reference Figure 1 A preparation process of a corrosion-resistant external reflector housing, the preparation process comprising the following steps:
[0058] S1: First, weigh the raw materials for preparation, and weigh: 40 parts by weight of modified polyimide; 20 parts by weight of fluororubber powder; 15 parts by weight of nano titanium dioxide; 10 parts by weight of graphene nanosheets; 8 parts by weight of organic montmorillonite; 0.8 parts by weight of hindered phenol antioxidant; 0.6 parts by weight of benzotriazole ultraviolet absorber; 0.4 parts by weight of polyether modified silicone oil lubricant and 0.7 parts by weight of rare earth metal organic complex;
[0059] S2: Put the weighed modified polyimide, fluororubber powder and organic montmorillonite into a high-speed mixer, and stir at a speed of 800 to 1200 rpm for 5 to 10 minutes to preliminarily mix the components.
[0060] S3: Then, the nano-titanium dioxide and graphene nanosheets are slowly added into the high-speed mixer, and the rotation speed is adjusted to 1000-1500 rpm, and stirring is continued for 8-15 minutes to ensure that the nano-materials are evenly dispersed in the mixture to prevent agglomeration.
[0061] S4: Add hindered phenol antioxidant, benzotriazole UV absorber, polyether modified silicone oil lubricant and special functional additive rare earth metal organic complex into the high-speed mixer in sequence, and stir at a speed of 1200-1800 rpm for 3-8 minutes to fully blend all additives with the previous mixture.
[0062] S5: The uniformly mixed material is conveyed to the hopper of a twin-screw extruder through a vacuum feeding device, the screw aspect ratio of the twin-screw extruder is set to 30-40:1, the temperature of each zone is set at 280-320°C, the screw speed is controlled at 200-300 rpm, and melt blending extrusion granulation is performed to obtain modified plastic particles.
[0063] S6: Place the extruded granules in a vacuum drying oven and dry them at 80-100°C for 4-6 hours to remove moisture and residual volatiles in the particles to ensure the stability of subsequent processing and product quality.
[0064] S7: Add the dried particles into the barrel of an injection molding machine, set the barrel temperature of the injection molding machine to 300-350° C., control the mold temperature to 80-120° C., set the injection pressure to 60-100 MPa, adjust the injection speed to 30-60 mm / s, perform injection molding operation, and obtain a blank of an external reflector housing.
[0065] S8: Deburr the blank after injection molding by grinding, polishing and other processes to make the shell surface smooth and flat without obvious defects and flash.
[0066] S9: Perform quality inspection on the mirror housing after deburring, including appearance inspection (for cracks, deformation, color difference, etc.), dimensional accuracy measurement (compared with design drawing requirements) and performance testing (such as corrosion resistance test, impact resistance test, etc.). Qualified products are packaged and put into storage, and unqualified products are classified and marked, and the reasons are analyzed. They are reworked or scrapped as appropriate.
[0067] In step S1, the hindered phenol antioxidant is antioxidant 1076 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate).
[0068] Benzotriazole UV absorbers such as UV absorber UV-329 (2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole);
[0069] Rare earth metal organic complexes can be complexes formed by rare earth lanthanide metals (such as lanthanum, cerium, etc.) and organic ligands (such as acetylacetone, citric acid, etc.)
[0070] In step S2, the mixing chamber of the high-speed mixer is cleaned and dried in advance to prevent impurities from mixing in and affecting the material properties. The mixer blades are designed with a specific forward tilt angle of 30 degrees and a twist of 45 degrees, which can generate strong convection and shear force when rotating, ensuring that the three raw materials are initially evenly dispersed in a short time. The mixing process is carried out in a closed environment to reduce the contact between the raw materials and the outside air and prevent moisture absorption or oxidation from causing changes in the raw material properties.
[0071] In step S3, when adding the nanomaterial, a high-precision micro-feeding device is used to accurately control the feeding amount at a speed of 2 g / s, so that the nanomaterial slowly and evenly enters the material flow in the high-speed mixer. Since the nanomaterial has a large specific surface area and high surface energy and is easy to agglomerate, nitrogen is intermittently introduced during the stirring process, and the gas flow rate is stabilized at 8 liters / minute. The agglomerates that may be formed are broken up by air flow disturbance, while protecting the raw materials from oxidation.
[0072] In step S4, when adding additives, the interval between adding each additive is set to 1.5 minutes so that the previous additive can be better dispersed in the material. During high-speed stirring, the temperature inside the mixer rises due to frictional heat. The temperature is controlled by the cooling jacket to maintain the mixing temperature at 50°C to prevent the additives from decomposing or volatilizing due to high temperature, ensuring that their effective ingredients can fully exert their effects.
[0073] In step S5, the screw structure of the twin-screw extruder adopts a specific combined design, including the conveying section adopting equidistant and unequal depth thread elements, the mixing section adopting a combination of kneading blocks and reverse thread elements, and the homogenizing section adopting toothed disc elements. The geometric shape and arrangement of the screw elements in each section are optimized according to the material characteristics to achieve efficient melting, mixing and homogenization effects. During the extrusion process, the vacuum degree is maintained at -0.07MPa to remove bubbles and volatiles in the material and improve the density and quality stability of the particles.
[0074] In step S6, the vacuum system of the vacuum drying oven uses a vacuum pump combined with a 50-liter vacuum buffer tank to stably maintain the vacuum degree in the drying oven. Six shelves are set inside the drying oven, and the particles are evenly spread on the shelves, with a layer spacing of 8 cm to ensure uniform heat transfer and full volatilization of moisture. The drying oven is equipped with a temperature sensor and a humidity sensor to monitor and control the temperature and humidity changes during the drying process in real time to ensure the best drying effect.
[0075] In step S7, the barrel of the injection molding machine adopts zone heating control, which is divided into 5 heating zones from the hopper end to the nozzle end. The temperature of each zone is set to 280℃, 300℃, 320℃, 330℃, and 340℃ respectively, to ensure that the material is evenly heated and gradually melted in the barrel, and injected into the mold cavity at the appropriate temperature and pressure. The mold is manufactured using high-precision processing technology, and the mold surface is polished and chrome-plated. The surface roughness reaches Ra1.2 microns, ensuring that the shell surface after injection molding is smooth, easy to demold, and has good appearance quality.
[0076] In step S8, according to the shape and precision requirements of different parts of the shell, 150-mesh coarse sandpaper is first used to remove large flash and burrs, and then 400-mesh fine sandpaper is used for fine grinding to make the surface roughness reach Ra0.6 microns. The polishing process uses polishing paste and polishing wheel, and the polishing wheel speed is controlled at 2000 rpm. By adjusting the polishing time to 10 minutes and the pressure to 0.5MPa, the shell surface achieves a mirror gloss effect to meet the appearance decorative requirements.
[0077] In step S9, a high-precision three-dimensional coordinate measuring instrument is used for dimensional accuracy measurement to accurately measure the key dimensions of the shell (such as length, width, thickness, aperture, etc.). The measurement accuracy can reach ±0.01 mm. The measurement results are compared with the tolerance requirements of the design drawings to determine whether they are qualified. The corrosion resistance test uses a corrosion test chamber that simulates the actual use environment. The shell is placed in a mist environment containing corrosive media such as 5% sulfuric acid, 3% sodium hydroxide, and 5% sodium chloride. The test lasts for 480 hours, and the degree of corrosion on the surface of the shell is observed. The corrosion resistance level is assessed according to relevant standards. The impact resistance test uses a drop hammer impact tester to drop a 1 kg drop hammer freely from a height of 1 meter to impact a specific part of the shell to observe whether the shell is broken or permanently deformed, so as to evaluate whether its impact resistance meets the requirements.
[0078] In the present invention, the tiny particles of nano-titanium dioxide and graphene nanosheets are intertwined and interspersed with each other, avoiding the occurrence of agglomeration, so that the subsequent molding process can be carried out smoothly based on a uniform raw material basis, ensuring the consistency and stability of product quality. In the melt blending stage, together with other materials such as modified polyimide, the ultraviolet shielding function of nano-titanium dioxide can effectively reduce the damage of ultraviolet rays to the material molecular chain in this process, maintain the stability of the material system, prevent the abnormal change of melt viscosity caused by light aging, and ensure the continuity and efficiency of the extrusion granulation process. At the same time, the high thermal conductivity of graphene nanosheets helps the uniform transfer of heat in the material, avoids local overheating and causes material performance differences, and is conducive to the formation of high-quality modified plastic particles.
[0079] In the present invention, in the injection molding process, the combination of nano-titanium dioxide and graphene nanosheets enhances the fluidity and filling of the material, so that the material can fill the mold cavity more accurately, reduce molding defects, and improve the dimensional accuracy and appearance quality of the product. During the use of the molded shell, the photocatalytic self-cleaning properties of nano-titanium dioxide and the antistatic and high-strength properties of graphene nanosheets continue to play a role. The photocatalytic effect keeps the shell surface clean and reduces the adhesion of corrosive media. The antistatic property prevents dust from adsorbing and carrying corrosive substances. The high strength ensures the stability of the shell structure, which significantly improves the corrosion resistance, stain resistance and durability of the shell, greatly prolongs the service life of the reflector shell, reduces the maintenance cost and frequency, and enables the product to always maintain good performance in a complex and changeable external environment.
[0080] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the term "comprise" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0081] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A process for preparing a corrosion-resistant external reflector housing, characterized in that: The preparation process comprises the following steps: S1: First, weigh the raw materials for preparation, and weigh: 30-40 parts by weight of modified polyimide; 15-20 parts by weight of fluororubber powder; 10-15 parts by weight of nano titanium dioxide; 5-10 parts by weight of graphene nanosheets; 4-8 parts by weight of organic montmorillonite; 0.5-0.8 parts by weight of hindered phenol antioxidant; 0.3-0.6 parts by weight of benzotriazole ultraviolet absorber; 0.2-0.4 parts by weight of polyether modified silicone oil lubricant and 0.3-0.7 parts by weight of rare earth metal organic complex; S2: Put the weighed modified polyimide, fluororubber powder and organic montmorillonite into a high-speed mixer, and stir at a speed of 800 to 1200 rpm for 5 to 10 minutes to preliminarily mix the components; S3: Then, the nano-titanium dioxide and graphene nanosheets are slowly added to the high-speed mixer, and the speed is adjusted to 1000-1500 rpm, and stirring is continued for 8-15 minutes to ensure that the nano-materials are evenly dispersed in the mixture to prevent agglomeration; S4: Add hindered phenol antioxidant, benzotriazole UV absorber, polyether modified silicone oil lubricant and special functional additive rare earth metal organic complex into a high-speed mixer in sequence, and stir at a speed of 1200 to 1800 rpm for 3 to 8 minutes to fully blend all additives with the previous mixture; S5: conveying the uniformly mixed materials to the hopper of a twin-screw extruder through a vacuum feeding device, setting the screw aspect ratio of the twin-screw extruder to 30-40:1, setting the temperature of each zone to 280-320° C., and controlling the screw speed to 200-300 rpm to perform melt blending, extrusion and granulation to obtain modified plastic particles; S6: placing the extruded granulated particles in a vacuum drying oven and drying them at 80-100° C. for 4-6 hours to remove moisture and residual volatiles in the particles to ensure the stability of subsequent processing and product quality; S7: adding the dried particles into the barrel of an injection molding machine, setting the barrel temperature of the injection molding machine to 300-350° C., controlling the mold temperature to 80-120° C., setting the injection pressure to 60-100 MPa, adjusting the injection speed to 30-60 mm / s, and performing an injection molding operation to obtain a blank of an external reflector housing; S8: Deburring the blank after injection molding, using grinding and polishing processes to make the shell surface smooth and flat without obvious defects and flash; S9: Perform quality inspection on the deburred reflector housing, including appearance inspection, dimensional accuracy measurement and performance test. Qualified products are packaged and put into storage, while unqualified products are classified and marked, and the reasons are analyzed. They are reworked or scrapped as appropriate.
2. The process for preparing a corrosion-resistant external reflector housing according to claim 1, characterized in that: In step S1, the hindered phenol antioxidant is selected from antioxidant 1076; Benzotriazole UV absorbers such as UV absorber UV-329; Rare earth metal organic complexes are complexes formed by rare earth lanthanide metals and organic ligands.
3. The process for preparing a corrosion-resistant external reflector housing according to claim 1, characterized in that: In step S2, the mixing chamber of the high-speed mixer is cleaned and dried in advance to prevent impurities from mixing in and affecting material properties; the mixer blades are designed with a specific forward tilt angle of 30 degrees and a twist of 45 degrees, which generates strong convection and shear force when rotating, ensuring that the three raw materials are initially evenly dispersed in a relatively short time.
4. The process for preparing a corrosion-resistant external reflector housing according to claim 1, characterized in that: In step S3, when adding the nanomaterial, a high-precision micro-feeding device is used to accurately control the feeding amount at a speed of 2 g / s, so that the nanomaterial slowly and evenly enters the material flow in the high-speed mixer; since the nanomaterial has a large specific surface area, high surface energy and is easy to agglomerate, nitrogen is intermittently introduced during the stirring process, and the gas flow rate is stabilized at 8 liters / minute.
5. The process for preparing a corrosion-resistant external reflector housing according to claim 1, characterized in that: In step S4, when adding additives, the interval time for adding each additive is set to 1.5 minutes so that the previous additive can be better dispersed in the material; during the high-speed stirring process, the temperature inside the mixer rises due to frictional heat generation, and the temperature is controlled by the cooling jacket to maintain the mixing temperature at 50°C.
6. The process for preparing a corrosion-resistant external reflector housing according to claim 1, characterized in that: In the step S5, the screw structure of the twin-screw extruder adopts a specific combined design, including a conveying section using equidistant and unequal depth thread elements, a mixing section using a combination of kneading blocks and reverse thread elements, and a homogenizing section using toothed disc elements. The geometric shape and arrangement of the screw elements in each section are optimized according to the material properties to achieve efficient melting, mixing and homogenization effects; during the extrusion process, the vacuum degree is maintained at -0.07MPa.
7. The process for preparing a corrosion-resistant external reflector housing according to claim 1, characterized in that: In step S6, the vacuum system of the vacuum drying oven adopts a combination of a vacuum pump and a 50-liter vacuum buffer tank to stably maintain the vacuum degree in the drying oven; 6 layers of shelves are arranged inside the drying oven, and the particles are evenly spread on the shelves, and the layer spacing is maintained at 8 cm to ensure uniform heat transfer and sufficient volatilization of moisture; the drying oven is equipped with a temperature sensor and a humidity sensor to monitor and control the temperature and humidity changes in the drying process in real time to ensure the best drying effect.
8. The process for preparing a corrosion-resistant external reflector housing according to claim 1, characterized in that: In the step S7, the barrel of the injection molding machine adopts zone heating control, and is divided into 5 heating zones from the hopper end to the nozzle end. The temperatures of each zone are set to 280°C, 300°C, 320°C, 330°C, and 340°C, respectively, to ensure that the material is evenly heated and gradually melted in the barrel, and is injected into the mold cavity at a suitable temperature and pressure; the mold is manufactured using high-precision processing technology, the mold surface is polished and chrome-plated, and the surface roughness reaches Ra1.2 microns.
9. The process for preparing a corrosion-resistant external reflector housing according to claim 1, characterized in that: In step S8, according to the shape and precision requirements of different parts of the shell, 150-mesh coarse sandpaper is first used to remove larger flash and burrs, and then 400-mesh fine sandpaper is used for fine grinding to make the surface roughness reach Ra0.6 microns; the polishing process uses polishing paste and polishing wheel, the polishing wheel speed is controlled at 2000 rpm, and the polishing time is adjusted to 10 minutes and the pressure is 0.5 MPa.
10. The process for preparing a corrosion-resistant external reflector housing according to claim 1, characterized in that: In the step S9, the dimensional accuracy is measured by a high-precision three-dimensional coordinate measuring instrument to accurately measure the key dimensions of the shell, and the measurement accuracy can reach ±0.01 mm. The measurement result is compared with the tolerance requirements of the design drawing to determine whether it is qualified; the corrosion resistance test uses a corrosion test box that simulates the actual use environment, and the shell is placed in a fog environment containing 5% sulfuric acid, 3% sodium hydroxide and 5% sodium chloride corrosive media. The test time lasts 480 hours, the degree of corrosion on the shell surface is observed, and the corrosion resistance level is evaluated according to relevant standards.